2014
DOI: 10.1111/apm.12240
|View full text |Cite
|
Sign up to set email alerts
|

Nodal distribution, stage migration due to diameter measurement and the prognostic significance of metastasis volume in melanoma sentinel lymph nodes: a validation study

Abstract: To validate metastasis location, maximum metastasis diameter (MMD) measurement induced stage migration and the prognostic significance of total metastatic volume (TMV) in melanoma sentinel lymph nodes (SLNs). A new 227 patient SLN cohort examined by complete step sectioning (250 μm) was tested for TMV and MMD prognostic significance; metastasis location by three different three-level protocols (Central vs Peripheral vs Global); and potential treatment changing down-staging by two restricted five-level protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Although the high metastasis detection rates of extensive protocols are appealing, they may be a waste of resources. On the other hand, when streamlining an SN protocol to best possible cost benefit some metastases may be missed or changed to a smaller diameter if workload is reduced, which ultimately may affect the cancer treatment 3–5. However, the prognostic significance of micrometastases is unclear, with some studies suggesting that they may not have prognostic value,16–21 and other studies suggesting that even very small metastases may affect the prognosis negatively 22–24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the high metastasis detection rates of extensive protocols are appealing, they may be a waste of resources. On the other hand, when streamlining an SN protocol to best possible cost benefit some metastases may be missed or changed to a smaller diameter if workload is reduced, which ultimately may affect the cancer treatment 3–5. However, the prognostic significance of micrometastases is unclear, with some studies suggesting that they may not have prognostic value,16–21 and other studies suggesting that even very small metastases may affect the prognosis negatively 22–24.…”
Section: Discussionmentioning
confidence: 99%
“…If true, it may not be necessary to extensively examine the peripheral parts of the SN. Meanwhile, other studies have found that metastases were located throughout the parenchyma and that they were equally sized 4–6 21 26–28. Thus, examining both the central and the peripheral parts of the SN would ensure higher metastasis detection rates compared with only examining the central parts of the node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of procedures can be used to estimate quantitatively tumour burden in the SLN, such as the maximal number of metastatic foci within the node, the maximum size of the largest metastasis, the maximum depth from the capsule of the tumour deposit (tumour penetrative depth) and the percentage crosssectional area of the SLN involved by the tumour [3,14,16,30,33e39]. Some of these involve calculations at several levels [17,40].…”
Section: Guidance On Histopathological Interpretationmentioning
confidence: 99%